The dawn of organic electronics. - Forrest, S. (IEEE spectrum)
Organic semiconductors are poised to transform the world of circuit and display technology. Major electronics firms such as Philips and Pioneer, and smaller companies such as Cambridge Display Technology, Universal Display, and Uniax, are betting that the future holds tremendous opportunity for the low cost and sometimes surprisingly high performance offered by organic electronic and optoelectronic devices. Using organic light-emitting devices (OLEDs), organic full-color displays may eventually replace liquid-crystal displays (LCDs) for use with laptop and even desktop computers. Such displays can be deposited on flexible plastic foils, eliminating the fragile and heavy glass substrates used in LCDs, and can emit bright light without the pronounced directionality inherent in LCD viewing, all with efficiencies higher than can be obtained with incandescent light bulbs